Is Hydroxyurea Treatment Changing the Life of Children with Sickle Cell Disease? - Mohammed Ali Al Sabbah; Mahmoud Radaideh; Shafeeka Mohammed Saleh; Sura Ahmed Al-Doory; Amal Mahmoud Abdalqader; Fatima Farid Mir; Aya Mohammed (Dubai Medical Journal)
Background: Sickle cell disease (SCD) is a prevalent hemoglobinopathy involving sickled hemoglobin that causes multiorgan disease due to chronic recurrent vaso-occlusion and hemolysis. Fetal hemoglobin (HbF) being present showed reduction in disease severity, owing to which hydroxyurea has gained significant recognition. The latter’s exact mechanism of action is yet unknown, but it has been demonstrated that the resulting rise in HbF raises hemoglobin levels and lessens the incidence of acute chest syndrome and vaso-occlusive crises. In the United Arab Emirates, our study is the first to assess the effects of hydroxyurea therapy in pediatric SCD patients. Methods: We conducted a retrospective cross-sectional study on 100 patients aged 2–13 years who were diagnosed with SCD, under regular outpatient follow-up with pediatric hematology clinic and receiving hydroxyurea therapy for at least 2 years. Basic hematologic parameters, frequency of SCD complications, and need for blood transfusions were studied. Results: Our analysis has shown a statistically significant (p < 0.05) correlation between hydroxyurea therapy and improved baseline hemoglobin and HbF levels; it decreased the incidence of painful crises and acute chest syndrome episodes; reduced the demand for blood transfusions; and recorded no side effects (pancytopenia or liver function disturbance). Conclusions: This study is the first of its kind in the UAE, and our findings support those of international data. The use of hydroxyurea therapy in SCD significantly improved hematologic and clinical parameters, thus markedly improving the patient’s quality of life. The side-effect profile is also limited, which further supports the fact that hydroxyurea is a relatively safe drug.